Rheology and soft tribology of thickened dispersions aiming the development of oropharyngeal dysphagia-oriented products - Vieira, M. J. (2020)
Dysphagia is a swallowing disorder that mainly affects elderly but can be minimized by thickening of liquid foods. Flaxseed gum (FG) was studied as a potential alternative thickener for dysphagia patients in comparison to commercial thickeners based on xanthan gum (XG) and modified starch (MS). Rheological and tribological responses of biopolymer-based thickening solutions (0.75 â 3 % w/w) incorporated in different food matrices (water, orange-flavoured soy juice and skim milk) were recorded and correlated. In general, the increase in gums concentration led to increases in viscosity, viscoelastic properties and lubricating capacity. An opposite behavior was observed for the MS-based products, since an increase in concentration led to a lower increase in viscosity and viscoelastic properties but caused a decrease in the lubricating capacity. These results indicated that associating tribology to rheology is crucial to further define formulations with pleasant swallowing characteristics.